An analytical study for predicting incipient motion velocity of sediments under ice cover - Hongchun Luo; Honglan Ji; Zijian Chen; Bin Liu; Zhongshu Xue; Zhijun Li (Scientific Reports)
Abstract This study investigates the critical impact of incipient sediment motion on sediment transport estimation and riverbed evolution prediction. In this research, we examine the effects of ice cover on the vertical distribution of flow velocity, establishing a mathematical relationship between the vertical average flow velocities in open channel and ice-covered flows. This leads to the derivation of a formula for incipient motion velocity under ice cover. Additionally, the study analyzes the riverbed evolution process under ice jam conditions. The proposed formula is applicable to both open channel and ice-covered flows, effectively capturing the characteristics of incipient sediment motion for non-cohesive and cohesive sediments. The calculated incipient motion velocities closely align with the empirical data from existing literature. The study reveals that the roughness of ice cover significantly influences the incipient motion velocity of sediment, with higher ratios of ice cover roughness to riverbed roughness promoting sediment initiation under more favorable hydraulic conditions. Furthermore, the riverbed beneath ice jams experiences significant scouring. Field observations indicate that when ice jams form in localized sections of the river, the displacement of the main flow can substantially increase flow velocity in areas away from the ice jam, leading to scouring in non-ice-jammed areas and sedimentation in ice-jammed areas. The uneven distribution of ice jam is likely a critical factor contributing to discrepancies between theoretical predictions and observed outcomes. The complexity and limited data associated with the initiation of cohesive sediments pose challenges in validating the proposed formula for these sediment types.